2018
DOI: 10.1111/jcpt.12681
|View full text |Cite
|
Sign up to set email alerts
|

A case of severe hyponatremia due to linezolid-induced SIADH

Abstract: This is the second case of a linezolid-induced SIADH, diagnosed with a thorough work-up so to correctly differentiate between SIADH from other causes of hyponatremia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…On the other hand, ALB level but not Ccr was identified as an independent variable affecting the development of hyponatraemia, suggesting that the risk of hyponatraemia increases when ALB level is low (Table 4). Four cases of hyponatraemia while receiving LZD therapy have been reported 14‐17 . In two of the four cases, a contributing factor for hyponatremia has signalled strongly a syndrome of inappropriate antidiuretic hormone secretion (SIADH) 15,16 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, ALB level but not Ccr was identified as an independent variable affecting the development of hyponatraemia, suggesting that the risk of hyponatraemia increases when ALB level is low (Table 4). Four cases of hyponatraemia while receiving LZD therapy have been reported 14‐17 . In two of the four cases, a contributing factor for hyponatremia has signalled strongly a syndrome of inappropriate antidiuretic hormone secretion (SIADH) 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Four cases of hyponatraemia while receiving LZD therapy have been reported 14‐17 . In two of the four cases, a contributing factor for hyponatremia has signalled strongly a syndrome of inappropriate antidiuretic hormone secretion (SIADH) 15,16 . SIADH is a condition of unsuppressed antidiuretic hormone (ADH) secretion from the posterior pituitary gland despite reduced serum osmotic pressure, followed by hypotonia due to relative ADH excess and persistent hyponatraemia 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, our patient was also on a diuretic; however on a loop diuretic (bumetanide) not a potassium sparing diuretic. As diuretics are well known to cause hypoonatremia on their own it alone could not explain the observation of the sudden drop post initiation of linezolid in the study by Tanaka et al in addition to the other case reports identified [6,7,8] .Together with the improvement and rise in sodium levels upon discontinuation of linezolid described in the reported cases increase the likelihood of association.…”
Section: Discussionmentioning
confidence: 72%
“…There are certain medications with well-known mechanism to cause hyponatremia and can affect the sodium and water homeostasis such as diuretics, or affect water homeostasis via increasing hypothalamic production of ADH such as antidepressants [5] . Hyponatremia is not a labeled adverse drug reaction with linezolid, our search of the literature identified three case reports and a retrospective cohort study that reported the incidence of hyponatremia in a cohort of 61 Japanese patients receiving linezolid [6,7,8,9] .…”
Section: Introductionmentioning
confidence: 99%